Frontispiece: Terminal Ligand and Packing Effects on Slow Relaxation in an Isostructural Set of [Dy(H2dapp)X2]+ Single Molecule Magnets. Issue 61 (3rd November 2021) - Pfleger, Rouven F.; Schlittenhardt, Sören; Merkel, Marcel P.; Ruben, Mario; Fink, Karin; Anson, Christopher E.; Bendix, Jesper; Powell, Annie K.
Abstract : The nature of the three chairs on the sandy beach indicate how easy it is for a system e. g. a person to relax when sitting on these. The length of time you might want to relax on these chairs is indicated by the speed of which the hourglasses have filled up. For the most comfortable chair the person is relaxing at leisure further helped by the nature of the phonon bath represented by the sand and the sea. However, additional relaxation via the phonon bath is also important which depends on the presence or absence of intermolecular interactions. This is illustrated at the shoreline by the series of chains, the first is a loose chain indicating relatively weak intermolecular interactions, a tight intermolecular interaction shown by a taut second chain and no significant intermolecular interactions shown by the broken chain. Read more in the Full Paper by A. Powell, J. Bendix et al. on page 15085 ff .